CD Companion Introduction. Power and Responsibility: Converted to Streaming Between Machines. - Van Belle, Guy (Leonardo Music Journal, 1999)
Focuses on the impact of information systems in the creation and performance of music. Role of Internet composers and music software developers; Development of multimedia authoring programs; Socio-cultural impact of computer music.